Impiego della tecnologia laser scanner su mezzo mobile terrestre per il city modelling - Vassena, Giorgio; Bonacina, Costante; Zinelli, Matteo (GEOmedia, 2009)
Use of laser scanner on mobile equipment for city modelling The use of GPS/INS systems on mobile instrumental equipment for 3D city modelling is more and more widespread as advanced technology of survey. These systems offer good versatility, even if with some problems linked to urban canyon and to the drift of inertial systems. In urban contest it seems also profitable the employment of classical topographic equipment for surveying of position of mobile mean in the 3D and colour data acquisition phase. This technology, easy to use, guarantees a good efficacy on urban scale and accuracies of alignment comparable to those of consolidated technology. The employment of equipment commonly available from operators makes the method proposed economically favourable, results being equal.